Sub-glottic cysts causing upper airway obstruction - Chigicherla, Swathi; Tewari, Shruti; Sharma, Rahul Deo; Nathani, Rajesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Wigger and Tang reported the first case of a sub-glottic cyst (SGC) in 1968. SGC are rare but potentially reversible causes of upper airway obstruction, in previously intubated children. These children present with respiratory distress and stridor, and the diagnosis is confirmed by direct laryngoscopy. The management depends on the size of the cysts and the severity of the symptoms. We are presenting two cases of SGCs who were born prematurely and were intubated for a prolonged period. They presented with stridor and were diagnosed to have sub-glottic cysts at bronchoscopy.